Efeitos do treinamento aeróbio no conteúdo da proteína utrofina e nas propriedades contráteis do músculo tibial anterior de camundongos mdx: modelo experimental da Distrofia Muscular de Duchenne - Araújo, Tatiana Oliveira Passos de (2020)
Introduction: Duchenne muscular dystrophy (DMD) is the most common and severe muscular dystrophy caused by the absence of the dystrophin protein that determines, progressive loss of muscle fibers and muscle weakness. It is a disease that has no cure, numerous studies seek palliative treatments that can mitigate the effects of the disease and provide a better quality of life for the patient. Low-intensity aerobic exercise has shown promising results in the rehabilitation of dystrophic skeletal muscle due to the content of utrophin protein, a protein homologous to dystrophin. However, there are few scientific reports that involve analysis of utrophin content after a long period of low-intensity aerobic training in dystrophic muscles. Therefore, our objective was to evaluate the impact of low-intensity aerobic training on the content of utrophin protein, in the anterior tibial muscle of mdx mice. Methods: 36 male mice were used, 12 Wild Type C57BL-10 animals (n = 6 / sedentary groups 21 and 37) and 24 mdx C57BL / 10-Dmdmdx animals (n = 6 / sedentary groups 21 and 37 and n = 6 / trained groups 21 and 37 sessions). The animals were submitted a low intensity running sessions (21 and 37) on a flat treadmill, and during the period grip strength test was performed. After the sessions, the animals were euthanized, and blood samples were obtained for analysis of the protein creatine kinase (CK), and the anterior tibial muscle excised for morphological and biochemical analysis. Results: The mdx animals showed a significant reduction in strength and utrophin content, important morphological changes, such as: necrosis, concomitant to the increase in CK, when compared to Wild Type animals. After 21 and 37 training sessions, there was an improvement in handgrip strength and morphological aspects, and an increase in utrophin content when compared to sedentary mdx animals. However, the animals submitted to the 37 of training showed more significant improvements when compared to those trained for 21 sessions. Conclusion: The maintenance of training for a long period has been shown to stimulate the increase in the content of utrophin protein, improve the function and morphology of the anterior tibial muscle of mdx mice.